Leadership Life Skills Development in 4-H Teen Leadership Programs - Amy M. Leman; Junfeng Wang ([TEST] Journal of Extension, 2021)
This study introduces a framework for 4-H leadership competencies and explores the relationship between 4-H leadership programs and participant leadership life skills development. Illinois 4-H members aged 15-18 completed an online survey about their 4-H experiences and skills. Participants reported local programs exhibited the characteristics in the leadership competencies framework. Members participating in leadership competency programs reported higher leadership life skills scores than those in other 4-H non-leadership oriented programs. Females reported higher leadership life skills scores in comparison to males. However, spending more years in leadership programs was only related to a significant change in skills development for some participants.
Keywords: 4-H leadership programs; youth leadership; life skills development; teen programming